THE USE OF MIND MAPPING TECHNIQUE IN WRITING DESCRIPTIVE TEXT - Nurlaila, Alma Prima (2013)
ABSTRACT This paper reports on the study concerned with investigating the use of mind mapping technique in teaching writing Descriptive texts to seventh-graders in a Junior High School in Bandung. This research aimed to investigate the effect of using mind mapping technique on students' writing ability and to discover the students' responses toward this technique in writing class. This research used mixed method. To gain quantitative data, pre-experimental design particulary one group pretest-posttest design was employed. This research also employed a qualitative research design by using questionnaire and interview techniques. The data from pretest and posttest were then analyzed by using a paired sample t-test on SPSS 16.0 for windows. The computation results of dependent t-test indicates that tobt is higher than tcrit (7.821 > 2.021) at the level significance 0.05 (two-tailed) which indicates that the alternative hypothesis (HA) is accepted. It means that there is a significant difference between students' pretest and posttest score after treatments. Furthermore, the results of questionnaires show that most students (86.1%) gave positive responses toward the use of mind mapping technique in writing Descriptive text. Finally, the result of interview suggest that the students loved this technique because it successfully motivated them to write Descriptive texts in an enjoyable way and to improve their writing Descriptive texts in terms of enriching vocabularies, increasing creativity, arranging sentences and organizing ideas. It is then recommended that mind mapping technique be used in teaching writing in different text types and levels of scholing. Keywods: mind mapping technique, writing, descriptive texts.